Assessing institutional dynamics of governance compliance in emerging markets: The GCC real estate sector - Rekha Pillai; Husam-Aldin Nizar Al-Malkawi; Muhammad Ishaq Bhatti (Journal of Risk and Financial Management, 2021)
The real estate sector has emerged as the bedrock of the Gulf Cooperation Council (GCC) economies, and it has remained resilient despite the various unprecedented micro- and macro-economic shocks devouring the world's economies. However, wavering investor attitudes and minimal exposure to real estate investment vehicles, coupled with weak regulatory frameworks, have led to dramatic downturns in the sector. Transparency about what is happening in real estate is imperative if the success of high-profile initiatives is to continue and much depends on good corporate governance (CG) in the sector. Using the most recent data from 2019, the current study applies the CG Index (CGI) and CG Deviation Index (CGDI) constructs to the real estate (RE) sector in the GCC in an effort to develop vital indicators for future RE investment decisions in the GCC region. The results indicate that the highest CG adherence levels are being achieved in Dubai, followed by Abu Dhabi and Saudi Arabia. The authors attribute these countries' success in CG adherence to the entrepreneurial identity of them RE firms as well as to their governance capacity, their socio-cognitive capability, and the level of regulatory enforcement within the context of their dominant governance logic. It should be noted that there are variations in adherence levels throughout each region. The results also agree with prior literature that a higher CGS leads to a lower CGD score, and vice versa. At this point, encouraging more real estate investment trust (REIT) formations in the GCC could ensure value propositions, such as liquidity, to both investors and RE companies as well as solid governance fundamentals. This is strongly recommended for increasing the RE presence and its contribution to the GDP of each country.
Keywords: G34; C43; N25; 330; real estate; corporate governance index; corporate governance deviation index; GCC countries